Martyrdom, sacrificial libation, and the eucharist of Ignatius of Antioch - Klawiter, Frederick C. (Lexington Books/Fortress Academic, 2022)
"Fred Klawiter argues that in Ignatius' eucharist, a wine libation symbolized the pouring out of Jesus' blood in his sacrificial death. By drinking from the libation cup in the eucharist/agape meal, Christians sought unity of agape with one another and the crucified, risen Jesus-while anticipating the possibility of martyrdom"--